2017
DOI: 10.1039/c7nr02243c
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight, highly thermally insulating and fire resistant aerogel by encapsulating cellulose nanofibers with two-dimensional MoS2

Abstract: Thermally insulating materials, made from earth-abundant and sustainable resources, are highly desirable in the sustainable construction of energy efficient buildings. Cellulose from wood has long been recognized for these characteristics. However, cellulose can be a flammability hazard, and for construction this has been addressed via chemical treatment such as that with halogen and/or phosphorus, which leads to further environmental concerns. Fortunately, the structure of cellulose lends itself well to chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 37 publications
2
65
2
Order By: Relevance
“…This fact suggested a synergistic effect between BA and MF on the flame retardant properties of CNF/MMT aerogels. The LOI value of the B/N FRA modified CNF‐based aerogels was much higher than those reported for flame retardant polymer‐based aerogels or foams, such as CNF/MoS 2 aerogel (LOI = 34.7%), PVA/MF aerogels (LOI = 36.5%), and PVA/MMT/APP (LOI = 42%) …”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…This fact suggested a synergistic effect between BA and MF on the flame retardant properties of CNF/MMT aerogels. The LOI value of the B/N FRA modified CNF‐based aerogels was much higher than those reported for flame retardant polymer‐based aerogels or foams, such as CNF/MoS 2 aerogel (LOI = 34.7%), PVA/MF aerogels (LOI = 36.5%), and PVA/MMT/APP (LOI = 42%) …”
Section: Resultscontrasting
confidence: 56%
“…Flame resistance is another important property expected for porous CNF aerogels that are highly flammable in nature. Inorganic phases have been introduced by in situ formation, physical blending, or layer by layer on the surface to form a char that acted like a barrier preventing burning of the underlying substrate. A synergistic flame retardant effect was achieved via incorporating clay and flame retardant agents (FRAs) or phosphorylation of CNF .…”
Section: Introductionmentioning
confidence: 99%
“…From a previous report, it is known that the weight loss could eliminate the low-molecular-weight species which adsorbed at the surface of cellulosic substrate if the polysiloxane is not bonded strongly to the CNF substrate [32]. Furthermore, the effective coating of the cellulosic substrate by a modifier can form an excellent physical barrier to prevent CNF from combustion [33]. Thus, the behaviors seen in this study, in which the temperature at 30% weight loss of HCNF/APP/MTMS aerogel was significantly delayed, indicate that the improvement of thermal stability was assigned to the inherent heat resistance of the polysiloxane bonded at the HCNF surface.…”
Section: Characterization Of Hcnf Hcnf/app and App/mtms/hcnf Aerogelsmentioning
confidence: 99%
“…On the one hand, MoS 2 has been used for enhancing the thermal, flame-retardant, and mechanical properties of polymer composites [18][19][20][71][72][73][74][75][76][77][78][79][80][81][82][83] due to its small size and high thermal stability. For instance, cellulose nanofibers (CNFs) were nano-wrapped with ultrathin 1T phase MoS 2 nanosheets via chemical crosslinking to produce an aerogel.…”
Section: Research Progress On Polymer/two-dimensional Nanomaterials Flmentioning
confidence: 99%
“…ermal and combustion characterization revealed highly desirable properties (thermal conductivity k = 28.09 mW m −1 K −1 , insulation R value = 5.2, limit oxygen index (LOI) = 34.7%, total heat release = 0.4 MJ m −2 ). Considering the inherently low density of this material, there was significant opportunity for its use in a number of insulating applications [72]. Wang et al reported the synthesis of MoS 2 nanosheets via a "thiol-ene" click reaction between defect-rich MoS 2 nanosheets with sulfydryl groups and ene-terminated hyperbranched polyphosphate acrylate (HPA), and characterized these nanosheets by FTIR and XPS to confirm their covalent functionalization through C-S bonds.…”
Section: Research Progress On Polymer/two-dimensional Nanomaterials Flmentioning
confidence: 99%